2016
DOI: 10.1111/zph.12328
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antimicrobial Resistance of Salmonella enterica Serovar Indiana in China (1984–2016)

Abstract: Salmonella enterica serovar Indiana, first described in 1955, is generally regarded as having a low frequency worldwide with outbreaks of gastroenteritis and abortions described in North America and Europe. In China, S. Indiana was first reported in 1984 and in the subsequent 71 surveys in 35 cities/municipalities from 18 provinces, 70% of which were after 2012, S. Indiana has been shown to have become widely prevalent in people, animals, food and the environment around abattoirs and meat processing facilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 47 publications
2
43
0
Order By: Relevance
“…The distribution of Salmonella serovars shows regional differences, (Gong et al, 2017). In this survey, we found that S. Indiana was the most prevalent serovar in raw meat, particularly in poultry (chicken and duck), which is similar to other reports T A B L E 2 Prevalence of Salmonella in raw meat that have indicated that poultry is an important reservoir of S. Indiana (Gong et al, 2017).…”
Section: Molecular Detection Technologies Have Become Popular Methodssupporting
confidence: 87%
See 3 more Smart Citations
“…The distribution of Salmonella serovars shows regional differences, (Gong et al, 2017). In this survey, we found that S. Indiana was the most prevalent serovar in raw meat, particularly in poultry (chicken and duck), which is similar to other reports T A B L E 2 Prevalence of Salmonella in raw meat that have indicated that poultry is an important reservoir of S. Indiana (Gong et al, 2017).…”
Section: Molecular Detection Technologies Have Become Popular Methodssupporting
confidence: 87%
“…Agona, to become the second most common serovar in the country, behind S . Enteritidis (Gong et al, ). In this survey, we found that S .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus analysis of antibiotic resistance is the crucial component of bacteriological diagnostics. Epidemiological studies of several hospitals in different cities of China revealed that resistance especially, multi-drug or pan-drug resistance kept increasing with the alarming rate ( Gong et al, 2017 ; He et al, 2017 ; Hu et al, 2017 ; Yang et al, 2017 ). Thus, the investigation of antibiotic resistance spectrum of diarrheal bacteria may provide important information for healthcare providers in proper treatments and taking measures to reduce drug resistance of bacteria.…”
Section: Introductionmentioning
confidence: 99%